Preparation method and application of modified triboelectric cellulose nanofiber membrane
By introducing Ti3C2Tx/MoS2 hybrid nanosheets into the cellulose-based friction layer, the modified triboelectric cellulose nanofiber membrane was synthesized, which solved the problems of insufficient performance of the cellulose-based friction nanogenerator and low air filtration efficiency, achieving high efficiency The effects of electrical output, multifunctional air filtration and health monitoring.
Patent Information
- Application Number
- CN202411381834.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the prior art, the development of cellulose-based friction layers used in friction nanogenerators is insufficient, which limits the high-performance development of cellulose-based friction nanogenerators. At the same time, the diffusion of suspended particles and the prevalence of respiratory diseases also require efficient air filtration. and health monitoring solutions.
Ti3C2Tx/MoS2 hybrid nanosheets were synthesized by hydrothermal reaction and grafted onto the surface of cellulose diacetate solution, and the modified triboelectric cellulose nanofiber membrane was synthesized by electrospinning and heat treatment. This membrane not only has strong electron de-electronic capacity, but also can efficiently filter submicron particles, and has near-infrared light sterilization and gas detection functions.
The high electrical output performance of cellulose nanofiber membrane in triboelectric generators is achieved, and the filtration efficiency of PM0.3, PM0.5 and PM1 is more than 98.5%. It has good durability and stability and can be used at high temperatures. Maintain filtration efficiency in high humidity environments and have the ability to respond quickly and accurately detect.
Smart Images

Figure CN119465504A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of efficient utilization of cellulose and nano energy, and specifically relates to a preparation method of a modified triboelectric cellulose nanofiber membrane and application thereof. Background Art
[0002] With the development of society and the widespread use of electronic products, the problem of energy consumption has become increasingly serious. As a revolutionary energy conversion device, triboelectric nanogenerators can convert low-frequency mechanical energy that is widely present in nature into electrical energy. However, the insufficient development of cellulose-based friction layers for triboelectric nanogenerators has become a bottleneck restricting the development of high-performance cellulose-based triboelectric nanogenerators.
[0003] The proliferation of suspended particulate matter (PM) from various sources and the prevalence of respiratory diseases, exacerbated by events such as the COVID-19 pandemic, pose a major threat to health. Approximately 90% of inhalable particulate matter consists of particles with a diameter equal to or less than 1.0 μm (PM1.0), which are known to carry harmful substances directly into the alveoli, causing respiratory problems and allergies.
[0004] High-efficiency filters with smaller pore sizes are essential to prevent submicron particles from escaping, but they often increase airflow resistance, leading to increased energy costs. In addition, there is a growing need for self-powered healthcare devices that can both efficiently filter air and monitor health conditions in real time in challenging environments such as high temperature, high humidity, and exposure to toxic gases.
[0005] Triboelectric nanogenerators (TENGs) based on triboelectric and electrostatic induction have emerged as a promising energy harvesting technology. TENGs can convert low-frequency mechanical energy into electrical energy, and they are portable and environmentally friendly, so they have been successfully used in wearable electronic devices. TENGs do not produce ozone and show potential in air pollution control, especially in filters. Integrating TENGs into filters can generate static charges through breathing, enhancing the adsorption of fine particles. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a modified triboelectric cellulose nanofiber membrane.
[0009] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a modified triboelectric cellulose nanofiber membrane, characterized in that: comprising:
[0010] Synthesis of Ti3C2T via hydrothermal reaction x / MoS2 hybrid nanosheets;
[0011] Ti3C2T was synthesized by tetraethyl orthosilicate hydrolyzate x / MoS2 hybrid nanosheets were grafted onto the surface of cellulose diacetate solution, and finally electrospun and heat-treated to synthesize modified triboelectric cellulose nanofiber membrane.
[0012] As a preferred embodiment of the preparation method of the present invention, wherein: the Ti3C2T x The preparation method of the Ti3C2T / MoS2 hybrid nanosheets comprises: x , ammonium molybdate tetrahydrate, thiourea and glucose are mixed; the mixture is added into 5-20 mL of water and reacted at 160-220° C. for 6-20 hours.
[0013] As a preferred embodiment of the preparation method of the present invention, wherein: the Ti3C2T x 10~50mg, AMT accounts for Ti3C2T x The weight ratio is 10% to 300%, the weight ratio of thiourea to AMT is 1000% to 1500%, and the glucose is 25 to 100 mg.
[0014] As a preferred embodiment of the preparation method of the present invention, the preparation method of the cellulose diacetate solution includes dissolving CDA in a mixture of N,N-dimethylacetamide and acetone by weight to obtain a solution; wherein the mass of CDA is 0.6 to 2 g; and the weight ratio of N,N-dimethylacetamide to acetone is 0.5 to 3:1.
[0015] As a preferred scheme of the preparation method described in the present invention, wherein: the Ti3C2Tx / MoS2 hybrid nanosheets are grafted onto the surface of the cellulose diacetate solution by adding the hybrid nanosheets to the cellulose diacetate solution and stirring at 20-40°C for 10-24h; wherein the cellulose diacetate solution is 8-15mL.
[0016] As a preferred embodiment of the preparation method of the present invention, the preparation method of tetraethyl orthosilicate hydrolyzate comprises mixing TEOS, DMF, water and HCl in a weight ratio of 1:3.5:1 to 5:0.01, and then stirring at 70°C for 0.1 to 2h.
[0017] As a preferred embodiment of the preparation method of the present invention, wherein: the Ti3C2T x The grafting of MoS2 hybrid nanosheets onto the surface of cellulose diacetate solution is performed by mixing tetraethyl orthosilicate hydrolyzate with cellulose diacetate solution to which hybrid nanosheets are added in a weight ratio of 1:4-7 and stirring at 30-80°C for 0.1-2h.
[0018] As a preferred embodiment of the preparation method of the present invention, the electrospinning conditions are as follows: a 20-22G needle is used, a high voltage of 16-24 kV is used, and a spinning distance of 9-12 cm is used.
[0019] As a preferred embodiment of the preparation method described in the present invention, the heat treatment conditions are as follows: placing the nanofiber membrane in a tubular furnace, heating it at 150-200°C for 0.5-4h in a nitrogen or argon atmosphere, and then heating it at 220-260°C for 0.5-4h.
[0020] Another object of the present invention is to overcome the deficiencies in the prior art and to provide a method for preparing a modified triboelectric cellulose nanofiber membrane and to use the triboelectric cellulose nanofiber membrane in the positive triboelectric material of a triboelectric nanogenerator.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention endows the cellulose nanofiber membrane with a strong electron loss ability, making it a strong triboelectric positive electrode material that can replace animal hair, polyimide and nylon. After being assembled with the negative electrode material, the voltage is as high as 197V. Thanks to the dual effects of physical interception and electrostatic adsorption, it has a strong ability to resist PM. 0.3 、PM 0.5 The filtration efficiency of PM2.5 and PM1 exceeded 98.5%. 0.3 The filtration efficiency is still over 90%, willing to detect the health status of the human body.
[0023] (2) The cellulose nanofiber membrane of the present invention can achieve a 99.9% sterilization rate after 15 minutes under near-infrared light irradiation. After 9 washes, the antibacterial rate is still over 98%. It can accurately detect trace amounts of NH3 (0.1 ppm) and respond quickly, with a response rate of 86% to 100 ppm NH3 within 2 seconds, which can quickly warn of NH3 leakage.
[0024] (3) The process designed by the present invention has a short process flow, simple equipment, and low cost, and can significantly improve the filtering performance of medical insurance products. It not only provides an effective method for creating wearable self-powered medical and health care devices to cope with challenging environments, but also shows great potential in promoting the development of a new generation of flexible, environmentally friendly and multifunctional electronic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0026] Figure 1 Ti3C2T prepared in Example 1 of the present invention x / MoS2 characterization diagram, where Figure 1 (a) Ti3C2T x SAED pattern of / MoS2, Figure 1 (b) Ti3C2T x / XRD spectrum of MoS2, Figure 1 (c) Ti3C2T x HRTEM image of / MoS2.
[0027] Figure 2 This is a characterization diagram of cellulose nanofibers in Example 1 of the present invention, wherein: Figure 2 (a) is the SEM image of cellulose nanofibers. Figure 2 (b) is the Raman image of the cellulose nanofiber membrane. Figure 2 (c) is the XRD image of cellulose nanofibers. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0030] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0031] The raw materials in the examples of the present invention are all commercially available unless otherwise specified, as shown in Table 1 for details.
[0032] Table 1
[0033]
[0034] Example 1
[0035] (1) Preparation of cellulose nanofiber membrane
[0036] 2.0 g of LiF was dissolved in 40 mL (9 M) hydrochloric acid. Then, 2.0 g of Ti3AlC2 was added to the above mixture and reacted at 35 °C for 24 h. Afterwards, it was washed with deionized water until the pH value of the supernatant was > 6. Then, anhydrous ethanol was added to the precipitate and ultrasonicated for 1 h to x Finally, a stable dark green single-layer Ti3C2T x Thin slices.
[0037] Select the etched single layer Ti3C2T x Blended with ammonium molybdate tetrahydrate (AMT), thiourea and glucose. x The weight ratio of AMT to Ti3C2Tx is 10 mg, the weight ratio of thiourea to AMT is 150%, the ratio of thiourea to AMT is 1200%, and 40 mg of glucose is selected. The above blend is added into 8 mL of ultrapure water or deionized water, and reacted in a reactor at 190 ° C for 10 h to obtain a nano-hybrid sheet.
[0038] 1 g of CDA was dissolved in a mixture of N, N-dimethylacetamide and acetone at a weight ratio of 0.5:1. The mixed solution was 10 mL. The nanohybrid sheets prepared above were added to the solution and stirred at 20 °C for 15 h.
[0039] TEOS, DMF, water and HCl were mixed in a weight ratio of 1:3.5:2:0.01, and then stirred at 70°C for 0.2h; TEOS hydrolyzate was mixed with CDA mixed solution dispersed with nanohybrid sheets in a weight ratio of 1:5, and stirred at 40°C for 0.2h;
[0040] A 21G needle was selected, and the spinning distance was 11 cm at 16 kV high voltage to obtain the nanofiber membrane, which was then placed in a tubular furnace and heated at 180 °C for 2 h in a nitrogen atmosphere, and then heated at 240 °C for 2 h.
[0041] (2) Preparation of triboelectric nanogenerator
[0042] The cellulose nanofiber membrane prepared above was selected as the positive electrode of the friction nanogenerator, and the polyvinylidene fluoride and nano-barium titanate blended nanofiber membrane negative electrode, with a size of 9 cm 2, copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz.
[0043] (3) The open circuit voltage of the modified cellulose-based nanofiber membrane as a triboelectric nanogenerator based on this embodiment is 190 V. It can be seen that the electrical output performance of the triboelectric nanogenerator of this embodiment is significantly improved. 0.3 、PM 0.5 The filtration efficiency of PM2.5, PM3 and PM4 was 98.58%, 99.02% and 99.32% respectively. Even under the harsh conditions of high temperature and high humidity of 100℃ or 99%RH, the filtration efficiency can be maintained above 90%. After 8 cycles of "test-washing", the filtration efficiency of PM2.5 was 98.58%, 99.02% and 99.32% respectively. 0.3 The filtration performance is still over 94%. After 15 minutes of near-infrared light irradiation, the inhibition rate of Escherichia coli and Staphylococcus aureus reached 99.6%. The device can accurately detect trace NH3 (0.2ppm) and respond quickly, with a response rate of 82% to 100ppm NH3 within 2 seconds. Even after 8 cycles of "test-washing", the bactericidal property and ammonia responsiveness remain extremely stable. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed.
[0044] Comparative Example 1
[0045] (1) Preparation of cellulose nanofiber membrane
[0046] 1 g of CDA was dissolved in a mixture of N, N-dimethylacetamide and acetone in a weight ratio of 0.5:1, the mixed solution was 10 mL, and stirred at 20 °C for 15 h; a 21G needle was selected, and the spinning distance was 11 cm at 16 kV high voltage to obtain a nanofiber membrane, which was then placed in a tubular furnace and heated at 180 °C for 2 h in a nitrogen atmosphere, and then heated at 240 for 2 h.
[0047] (2) Preparation of triboelectric nanogenerator
[0048] The cellulose nanofiber membrane prepared above was selected as the positive electrode of the friction nanogenerator, and the polyvinylidene fluoride and nano-barium titanate blended nanofiber membrane negative electrode, with a size of 9 cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz. The open circuit voltage obtained was 65V.
[0049] Example 2
[0050] (1) Preparation of cellulose nanofiber membrane
[0051] 2.0 g of LiF was dissolved in 40 mL (9 M) hydrochloric acid. Then, 2.0 g of Ti3AlC2 was added to the above mixture and reacted at 35 °C for 24 h. Afterwards, the result was washed with deionized water several times until the pH value of the supernatant was > 6. Then, anhydrous ethanol was added to the precipitate and ultrasonicated for 1 h to x Finally, a stable dark green single-layer Ti3C2T x Thin slices.
[0052] Select the etched single layer Ti3C2T x Blended with AMT, thiourea and glucose. Ti3C2Tx is 12mg, AMT accounts for 12mg of Ti3C2Tx. x The weight ratio is 230%, the ratio of thiourea to AMT is 1300%, and 40 mg of glucose is selected. The above blend is added into 10 mL of ultrapure water or deionized water, and reacted in a reactor at 200° C. for 12 hours to obtain hybrid nanosheets.
[0053] 1.5 g CDA was dissolved in a mixture of N, N-dimethylacetamide and acetone at a weight ratio of 0.3:1. The mixed solution was 12 mL. The nanohybrid sheets prepared above were added to the solution and stirred at 30 °C for 20 h.
[0054] TEOS, DMF, water and HCl were mixed in a weight ratio of 1:3.5:1.5:0.01, and then stirred at 70°C for 0.4h; TEOS hydrolyzate was mixed with CDA mixed solution dispersed with nanohybrid sheets in a weight ratio of 1:6, and stirred at 40°C for 0.1h;
[0055] A 21G needle was selected, and the spinning distance was 10 cm at 18 kV high voltage to obtain the nanofiber membrane, which was then placed in a tubular furnace and heated at 200°C for 1 h in a nitrogen atmosphere, and then heated at 250°C for 3 h.
[0056] (2) Preparation of triboelectric nanogenerator
[0057] The modified cellulose fiber membrane prepared above was selected as the positive electrode of the friction nanogenerator, and the nanofiber membrane of polyvinylidene fluoride and nano-barium titanate was used as the negative electrode. The size was 9 cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz.
[0058] (3) The open circuit voltage of the modified cellulose-based nanofiber membrane used as a triboelectric nanogenerator in this embodiment is 180 V. It can be seen that the electrical output performance of the triboelectric nanogenerator in this embodiment is significantly improved. 0.3 、PM 0.5 The filtration efficiency of PM2.5, PM3 and PM1 are as high as 96.72%, 98.12% and 99.02% respectively. Even under the harsh conditions of high temperature and high humidity of 100℃ or 99%RH, the filtration efficiency can be maintained above 88%. After 6 cycles of "test-washing", the filtration performance of PM0.3 is still over 91%. After 15 minutes of near-infrared light irradiation, the antibacterial rate of Escherichia coli and Staphylococcus aureus reached 99.1%. The device can accurately detect trace amounts of NH3 (0.2ppm) and respond quickly, with a response rate of 81.3% to 100ppm NH3 within 5 seconds. Even after 8 cycles of "test-washing", the bactericidal property and ammonia responsiveness still maintain excellent stability. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed.
[0059] Comparative Example 2
[0060] (1) Preparation of cellulose nanofiber membrane
[0061] 1.5 g CDA was dissolved in a mixture of N, N-dimethylacetamide and acetone in a weight ratio of 0.3:1, the mixed solution was 12 mL, and stirred at 30 ° C for 20 h; a 21G needle was selected, and the spinning distance was 10 cm at 18 kV high voltage to obtain a nanofiber membrane, which was then placed in a tubular furnace and heated at 200 ° C for 1 h in a nitrogen atmosphere, and then heated at 250 ° C for 3 h.
[0062] (2) Preparation of triboelectric nanogenerator
[0063] The cellulose nanofiber membrane prepared above was selected as the positive electrode of the friction nanogenerator, and the polyvinylidene fluoride and nano-barium titanate blended nanofiber membrane negative electrode, with a size of 9 cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates respectively, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz. The open circuit voltage obtained was 61V.
[0064] Example 3
[0065] (1) Preparation of cellulose nanofiber membrane
[0066] 2.0 g of LiF was dissolved in 40 mL (9 M) hydrochloric acid. Then, 2.0 g of Ti3AlC2 was added to the above mixture and reacted at 35 °C for 24 h. Afterwards, the result was washed with deionized water several times until the pH value of the supernatant was > 6. Then, anhydrous ethanol was added to the precipitate and ultrasonicated for 1 h to x Finally, a stable dark green single-layer Ti3C2T x Thin slices.
[0067] Select the etched single layer Ti3C2T x Blended with AMT, thiourea and glucose. x is 15mg, AMT accounts for Ti3C2T x The weight ratio is 200%, the ratio of thiourea to AMT is 1500%, and 70 mg of glucose is selected. The above blend is added to 10 mL of ultrapure water or deionized water and reacted in a reactor at 220°C for 12 hours. 1.4 g of CDA is selected and dissolved in a mixture of N, N-dimethylacetamide and acetone with a weight ratio of 0.25:1. The mixed solution is 10 mL. The nanohybrid sheets prepared above are added to the solution and stirred at 35°C for 24 hours;
[0068] TEOS, DMF, water and HCl were mixed in a weight ratio of 1:3.5:2.3:0.01, and then stirred at 60°C for 1.1h; TEOS hydrolyzate was mixed with CDA mixed solution dispersed with nanohybrid sheets in a weight ratio of 1:4.5, and stirred at 0.5°C for 0.5h;
[0069] A 21G needle was selected, and the spinning distance was 11 cm at 20 kV high voltage to obtain the nanofiber membrane, which was then placed in a tubular furnace and heated at 180°C for 2 h in a nitrogen atmosphere, and then heated at 250°C for 3 h.
[0070] (2) Preparation of triboelectric nanogenerator
[0071] The modified cellulose aerogel prepared above was selected as the positive electrode of the friction nanogenerator, and the nanofiber membrane of polyvinylidene fluoride and nano-barium titanate was used as the negative electrode, with a size of 9 cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz.
[0072] (3) The open circuit voltage of the modified cellulose-based nanofiber membrane used as the friction nanogenerator in this embodiment is 185 V. It can be seen that the electrical output performance of the friction nanogenerator in this embodiment is significantly improved. 0.3 、PM0.5 The filtration efficiency of PM2.5, PM2.5 and PM1 are as high as 97.82%, 98.82% and 99.12% respectively. Even under the harsh conditions of high temperature and high humidity of 100℃ or 99%RH, the filtration efficiency can be maintained above 90%. After 9 cycles of "test-washing", the filtration performance of PM0.3 is still over 94%. After 15 minutes of near-infrared light irradiation, the antibacterial rate of Escherichia coli and Staphylococcus aureus reached 99.4%. The device can accurately detect trace amounts of NH3 (0.1ppm) and respond quickly, with a response rate of 82.3% to 100ppm NH3 within 6 seconds. Even after 9 cycles of "test-washing", the bactericidal property and ammonia responsiveness remain extremely stable. By monitoring the wearer's breathing status in real time, respiratory health status can be continuously assessed.
[0073] Comparative Example 3
[0074] (1) Preparation of cellulose nanofiber membrane
[0075] 1.4 g CDA was dissolved in a mixture of N, N-dimethylacetamide and acetone in a weight ratio of 0.25:1 and stirred at 35 °C for 15 h; a 21G needle was selected, and the spinning distance was 11 cm at 20 kV high voltage to obtain a nanofiber membrane, which was then placed in a tubular furnace and heated at 180 °C for 2 h in a nitrogen atmosphere, and then heated at 250 for 3 h.
[0076] (2) Preparation of triboelectric nanogenerator
[0077] The cellulose nanofiber membrane prepared above was selected as the positive electrode of the friction nanogenerator, and the polyvinylidene fluoride and nano-barium titanate blended nanofiber membrane negative electrode, with a size of 9 cm 2 , copper foil was covered on the back of the two triboelectric materials, and then fixed on acrylic plates respectively, and the wires were connected to the upper and lower electrodes. The contact separation power generation test of the triboelectric nanogenerator was carried out with a pressure of 10N and a frequency of 3Hz. The open circuit voltage obtained was 52V.
[0078] The corresponding selected area electron diffraction (SAED) pattern ( Figure 1 a) shows the diffraction spots and two diffraction rings, which are attributed to the hexagonal crystal structure of MXene and the (100) and (110) polycrystalline structures of MoS2, respectively. The characteristic peak corresponding to the (002) plane of MXene indicates that the crystal structure of MXene is retained after the hydrothermal reaction ( Figure 1b). In addition, the XRD spectrum of Ti3C2Tx / MoS2 shows new peaks at (002), (100), (103), (105), (110) and (201), which are attributed to MoS2, indicating the coexistence of Ti3C2Tx and MoS2 crystalline phases. From the high-resolution TEM (HRTEM) image of Ti3C2Tx / MoS2, it can be seen that the measured Ti3C2Tx lattice plane spacing is 0.36nm, corresponding to the (002) plane. In addition, the experimental results show that MoS2 nanosheets are few-layer crystals with a vertical structure. The lattice plane spacing is approximately 0.62nm and 0.12nm, corresponding to the (002) plane and (100) plane of MoS2, respectively ( Figure 1 c). These findings confirm that Ti3C2Tx and MoS2 coexist and form a heterojunction.
[0079] SEM images show that CTTM is composed of interwoven nanofibers and hybrid nanosheets dispersed in the fibers ( Figure 2 a). Raman spectroscopy shows that at 1100cm -1 The characteristic peaks of stretching vibration of glycosides in cellulose observed at the bottom of the column are retained after modification ( Figure 2 b) at 208 and 502 cm -1 (bending and torsional vibration of Si-O-Si), 442cm -1 (Bending vibration of O-Si-O) and 778 and 1100 cm -1 The peak corresponding to silicon dioxide (SiO2) at (Si-O stretching vibration) indicates that TEOS has been converted into SiO2.
[0080] CT, CTT and CTTM all retain the characteristic crystalline peak of CD at 17.8° (corresponding to the (200) plane) Figure 2 c). Compared with CD, the peak intensity of CT is slightly reduced, which may be due to the dehydration condensation of silanol and hydroxyl groups on the CD surface, resulting in a decrease in cellulose crystallinity. In addition, the characteristic SiO2 (101) plane peak at 21° was observed in CT, CTT, and CTTM. Figure 1 Compared with b, the diffraction peaks induced by Ti3C2Tx and Ti3C2Tx / MoS2 confirmed that the synthesis of CTT and CTTM did not significantly change the crystal structure of cellulose and CT during the modification process. XRD analysis further confirmed the conclusion of Raman spectroscopy. The above analysis shows that the cellulose nanofiber membrane was successfully synthesized.
[0081] The nanofiber membrane prepared by electrospinning of the present invention has a strong application scenario in the field of air filtration, and the friction nanogenerator forms an electrostatic field between two friction electric materials, which can polarize PM in the air and adsorb to the surface of the friction electric material. Therefore, the combination of the two can efficiently filter PM in the air. In extreme environments, such as fires, bacteria growth, high temperature and humidity, and toxic gas leakage are often accompanied. Therefore, there is an urgent need for a multifunctional air filtration device. For these complex environments, higher requirements are put forward for the development of new air filtration devices. MXene and MoS2 have photothermal properties and ammonia responsiveness, and form tightly bound MXene / MoS2 heterocyclic nanosheets through hydrothermal reaction. Moreover, the excellent conductivity of the nanohybrid sheet can improve the output performance of the friction nanogenerator. The conversion of TEOS to SiO2 at high temperature can not only improve the triboelectric performance, but also improve the material's resistance to high temperature and humidity.
[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a modified triboelectric cellulose nanofiber film, characterized in that: include, Synthesis of Ti3C2T via hydrothermal reaction x / MoS2 hybrid nanosheets; Ti3C2T was synthesized by tetraethyl orthosilicate hydrolyzate x / MoS2 hybrid nanosheets were grafted onto the surface of cellulose diacetate solution, and finally electrospun and heat-treated to synthesize modified triboelectric cellulose nanofiber membrane.
2. The preparation method according to claim 1, characterized in that: The Ti3C2T x The preparation method of the Ti3C2T / MoS2 hybrid nanosheets comprises: x , ammonium molybdate tetrahydrate, thiourea and glucose are mixed; the mixture is added into 5-20 mL of water and reacted at 160-220° C. for 6-20 hours.
3. The preparation method according to claim 2, characterized in that: The Ti3C2T x 10~50mg, AMT accounts for Ti3C2T x The weight ratio is 10% to 300%, the weight ratio of thiourea to AMT is 1000% to 1500%, and the glucose is 25 to 100 mg.
4. The preparation method according to claim 1, characterized in that: The preparation method of the cellulose diacetate solution comprises the following steps: dissolving CDA in a mixture of N,N-dimethylacetamide and acetone by weight to obtain the solution; wherein the mass of CDA is 0.6-2g; and the weight ratio of N,N-dimethylacetamide to acetone is 0.5-3:
1.
5. The preparation method according to claim 1, characterized in that: The Ti3C2T x The / MoS2 hybrid nanosheets are grafted onto the surface of the cellulose diacetate solution by adding the hybrid nanosheets into the cellulose diacetate solution and stirring at 20-40°C for 10-24 hours; wherein the cellulose diacetate solution is 8-15 mL.
6. The preparation method according to claim 1, characterized in that: The preparation method of tetraethyl orthosilicate hydrolyzate comprises mixing tetraethyl orthosilicate, DMF, water and HCl in a weight ratio of 1:3.5:1-5:0.01, and then stirring at 70° C. for 0.1-2 hours.
7. The preparation method according to claim 1, characterized in that: The Ti3C2T x The grafting of MoS2 hybrid nanosheets onto the surface of cellulose diacetate solution is performed by mixing tetraethyl orthosilicate hydrolyzate with cellulose diacetate solution to which hybrid nanosheets are added in a weight ratio of 1:4-7 and stirring at 30-80°C for 0.1-2h.
8. The preparation method according to claim 5, characterized in that: The electrospinning conditions are to use a 20-22G needle, 16-24kV high voltage, and a spinning distance of 9-12cm to obtain a nanofiber membrane.
9. The preparation method according to claim 5, characterized in that: The heat treatment conditions are as follows: placing the nanofiber membrane in a tubular furnace, heating it at 150-200° C. for 0.5-4 h in a nitrogen or argon atmosphere, and then heating it at 220-260° C. for 0.5-4 h.
10. Use of the triboelectric cellulose nanofiber film prepared by the preparation method according to claims 1 to 9 in the positive triboelectric material of a triboelectric nanogenerator.
Citation Information
Patent Citations
Method for improving tribological performance of epoxy resin
CN110105711A
Modified cellulose nanofibril-based flexible friction nano-generator
CN111082698A
Preparation method of nanocellulose / molybdenum disulfide piezoelectric composite film
CN112646236A
MXene / MoS2 heterojunction functional modified polymer film as well as preparation method and application thereof
CN114904401A
Enhanced flexible polyvinylidene fluoride nanofiber material and friction nano-generator
CN115491815A